Personal Knowledge Management of Jabodetabek Urban Community in Indonesia in Facing Digital Era - Laksmi Laksmi (Pustabiblia: Journal of Library and Information Science, 2021)
This study discusses how personal knowledge management in Jabodetabek urban community (stand for Jakarta, Bogor, Depok, Tangerang, Bekasi) in Indonesia, as a multi-ethnic nation with a thick oral culture is facing the digital era. The urgency of this research is to be able to build awareness and managing knowledge effectively in society. This research uses quantitative approach with case study method. Data is collected using the Google-form questionnaire between January-July 2018. Respondents are determined by non-probability sampling methods, obtained 224 respondents. The findings show that the strategy of gaining knowledge is at the highest level, while knowledge sharing is at the lowest level. In addition, the community has not fully utilized knowledge in this digital era. They focus on knowledge about hobbies, entertainment, and health. It was concluded that individuals who, on average, were students and office workers, showed effectiveness of knowledge management that were not optimally integrated, thus hampering the development of knowledge itself. Ideally individuals actively share knowledge for mutual progress, Jabodetabek communities are still passive, and sharing knowledge in close environment that are related to school or office assignments. This issue can be developed using a qualitative approach in order to gain deeper understanding of personal knowledge management from cultural perspective.